Issues in Economic Theory: an Attempt to Clarify - Homan, Paul T. (Quarterly Journal of Economics, 1928)
I. Controversies in economic theory are of varying importance, — The explanatory and instrumental aspects of economic theory, 335. — Changing facts and social theories, 337. — II. The place of “facts” in economic controversy, 339. — The relation of psychology to economic theory, 343. — Mechanistic and organic social theories as a source of controversy, 347. — Difficulties arising out of the organic analogy, 349. — III. The philosophy of “social control,” 351. — IV. Chaotic possibilities of “viewpoints” in economics, 355. — Uses and limitations of the mechanistic view, 356. — Types of new “approaches” to economics, and their limitations, 359. — Sacrifices entailed in eliminating controversies, 360. — The scientific character of economics, old and new, 362.